Electricity Access Threshold for Meeting Non-Energy SDG Targets - Brecha, Robert (European Journal of Sustainable Development, 2019)
Access to sufficient amounts of energy is a prerequisite for development of human well-being. Analysis presented in this paper shows that multiple sustainable development targets are linked to per capita access to electricity in particular and demonstrate a threshold behavior below which sustainable development targets have not been met historically. The present work relates to the broad literature on the Sustainable Development Goals (SDGs), recognizing the interconnectedness of energy access (SDG7) and other development goals. Although targets are provided for each of the 17 goals, not all targets are quantified, leaving room for ambiguity in fulfilling, for example, the goal of ?ensuring access to affordable, reliable, sustainable and modern energy for all.? The focus of this work is an extension of our previous finding that a per capita societal electricity consumption threshold of about 400kWh is strongly related to meeting outcomes for health indicators related specifically to SDG targets. In this contribution we further examine this quantitative relationship between electricity access as correlated with education, sanitation, food security and health outcomes, posing the question in the form, ?Below what minimum societal per capita access to electricity is a country very unlikely to meet SDG targets?